LAYANAN PERPUSTAKAAN DALAM MENINGKATKAN MUTU FAKULTAS HUKUM UNIVERSITAS SAM RATULANGI - ROTINSULU, LANI; KAWUNG, EVELIN; WALELENG, GRACE (JURNAL ADMINISTRASI PUBLIK, 2019)
library service is the core of all activities of the library. The success of an institution the libraryis highly determined by the quality of library services, which occurs in almost all low level library his visitor deserted from visitors, the service provided by the library are still less interested and utilized. Based onthe background of the problem then this research aims to analyze why the library services are notattractive to and utilized by users, as well as a review of library services in improving the quality of theFaculty of law The University Of Sam Ratulangi.This research uses descriptive qualitative approach. The technique of Data collection is the empirical factscollected by the Researcher for the purpose of solving a problem or answer a question of research. In thisstudy using this type of primary data and secondary data. Primary data is data that is directly recorded onsite research through an in-depth interview obtained through observations conducted by the Researchersthemselves. Secondary data is data processed or the data has been published officially obtained from newsmedia, documentation and archive instances related to library services.The results showed that that the elements supporting the activities of the service in the library of theFaculty of law of the University of Sam Ratulangi inadequate compliance with the expectations of theuser, it is visible on the facilities, collections, librarians and users still very minimalKeywords: Services, library